2019
DOI: 10.1002/jsfa.10094
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition of Tempranillo Blanco (Vitis vinifera L.) grapes and wines after biostimulation via a foliar seaweed application

Abstract: BACKGROUND Seaweeds are defined as novel elicitors in many crops, allowing the synthesis of secondary metabolites to be triggered in different plant tissues. Currently, the phenolic composition of Tempranillo Blanco grapes and wines is unreported. The present study aimed to investigate the effects of an Ascophyllum nodosum seaweed extract applied to Tempranillo Blanco grapevines, at low (Ld) and high (Hd) dosages, on grape and wine phenolic compounds during two consecutive seasons (2017–2018). RESULTS The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
2
11
0
2
Order By: Relevance
“…In 2018, control wines presented higher alcohol degree than Hd samples, and higher pH than Ld samples. These results are similar to those exposed by certain authors, who showed scarce effects on must and wine physico‐chemical parameters after the application of seaweeds to the grapevines 14,15,17–20,26 . Volatile acidity was higher in the wines produced in 2018 than in 2017, probably due to the duration of the MLF.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In 2018, control wines presented higher alcohol degree than Hd samples, and higher pH than Ld samples. These results are similar to those exposed by certain authors, who showed scarce effects on must and wine physico‐chemical parameters after the application of seaweeds to the grapevines 14,15,17–20,26 . Volatile acidity was higher in the wines produced in 2018 than in 2017, probably due to the duration of the MLF.…”
Section: Resultssupporting
confidence: 91%
“…These results are similar to those exposed by certain authors, who showed scarce effects on must and wine physico-chemical parameters after the application of seaweeds to the grapevines. 14,15,[17][18][19][20]26 Volatile acidity was higher in the wines produced in 2018 than in 2017, probably due to the duration of the MLF. According to the multifactorial analysis (MFA), treatment affected probable alcohol and pH in musts and wines.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Yeast-Assimilable Nitrogen (YAN) levels in grape musts are important for ensuring a healthy fermentation. Grape musts with suboptimal YAN levels can often result in sluggish or stuck fermentations and the development of off flavours in the resulting wines [79]. Moreover, one of the many factors influencing the final quality of fermentation is determined by the nitrogen levels of the berries at harvest [80].…”
Section: Effects On Winemakingmentioning
confidence: 99%